Making the 'Local' Visible in Social Work Education: Insights from Nigeria and Scotland on (Re)balancing and Contextualising Indigenous and International Knowledge. (19th February 2022) - Levy, Susan; Okoye, Uzoma O; Ingram, Richard
Abstract: Social work in the twenty-first century is maturing as a global profession. This comparative study offers an original contribution to the evolving discussion in the field of international social work. The paper makes visible the socio-spatial dimensions and contested interpretations of international and indigenous knowledge through the experiences of social work students in the Global South and Global North. Drawing on findings from an online survey completed by undergraduate and postgraduate Nigerian and Scottish social work students ( n  = 142), the paper provides insights into the students' experiences, expectations and perceived challenges. The Nigerian students critiqued the international (Western) knowledge informing their learning and practice, questioned the absence of indigenous knowledge and were aware of the importance, and challenges, of working with cultural diversity. The Scottish students showed little criticality of the Western (local) knowledge underpinning their learning and practice, did not prioritise learning about international social work and highlighted tensions between working with a culture of neoliberalism and social work values and social justice. We call for raising awareness of the epistemological foundations of what is included/excluded in curriculum and why, making the 'local' visible through re-balancing and contextualising the use of international and indigenous knowledge within social work. Abstract : This study presents new thinking on how international and indigenous social work knowledge are used in social work. The paper draws on findings from an online survey completed by 142 undergraduate and postgraduate Nigerian and Scottish social work students. Key findings: International social work was defined and taught differently in each university. For Nigerian students international (Western) knowledge was central to their studies, for Scottish students international (indigenous) knowledge was peripheral to their studies. Nigerian students highlighted that Western/international knowledge dominated their learning but could not always be applied to their practice. The students called for more indigenous knowledge to better prepare them for practice. Scottish students showed little criticality of the knowledge informing their learning as local/Western and did not identify international social work as a priority area for study. Challenges associated with applying social work knowledge in practice led Nigerian students to focus on working with cultural diversity, whilst Scottish students highlighted regulation and neoliberalism. (Re)balancing and contextualising the use of international and indigenous knowledge in social work education is recommended. To be achieved through making local knowledge visible in the Global North and Global South; and building the empirical foundation of social work in the Global South.